Evidências científicas sobre amputação de membros inferiores em pessoas com diabetes mellitus - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Objective: To identify the scientific evidence on lower limb amputation in people with diabetes mellitus. Methodology: an integrative review composed of six stages, the data collection being carried out in the month of April 2019, with search in the Latin American and Caribbean Literature in Health Sciences database (LILACS), using the advanced form as search strategy: “Diabetes Mellitus ”or“ Diabetes Mellitus type 1 ”or“ Diabetes Mellitus type2 ”or“ Diabetes ” [Words] and “Amputations” or “Amputation Stumps” or “Amputation” [Words]. Results: Three categories were identified by reading the publications: Profile, Risk factors and comorbidities associated with lower limb amputation Diabetes Mellitus; Prevention and health promotion strategies to prevent amputation due to DM and experiences and feelings after amputation due to DM. Conclusion: The most frequent evidence related to the profile was male and older to 60 years, the comorbidity highlighted in the studies was smoking and hypertension Systemic Arterial System (SAH). In addition, the importance of the patient being assiduous in consultations with the change of life habits are the main elements for prevention of amputations due to DM. In post-amputation experiences, the feelings of sadness, suffering due to limb loss, fear / trauma of living a new amputation.
Scientific evidence on lower limb amputation in people with diabetes mellitus
Keywords: Enfermagem; Amputation; Diabetes Mellitus; Amputação; Nursing; CNPQ::CIENCIAS DA SAUDE